Miniature Erupting Volcano-Shaped Mitral Valve Aneurysm Secondary to Streptococcus agalactiae ST1656 Endocarditis: A Case Report - Yamamoto, Hiroyuki; Yamada, Hiroyuki; Maeda, Takahiro; Goto, Mieko; Ikeda, Yoshihiko; Takahashi, Takashi (Frontiers in Cardiovascular Medicine, 2021)
Mitral valve aneurysm (MVA) is a rare but life-threatening valvular pathologic entity most commonly associated with infective endocarditis (IE) of the aortic valve (AV). We describe a diabetic patient with ruptured anterior MVA secondary to capsular genotype V Streptococcus agalactiae (GBS) harboring novel ST1656 IE without AV involvement. Our patient presented with manifestations of various serious systemic and intracardiac complications, requiring early surgery, but ultimately died from non-cardiogenic causes. This case emphasizes the importance of treating MVA as a dangerous sequela of IE, of performing transesophageal echocardiography to make its accurate diagnosis and institute early surgical intervention, and of considering GBS as a rare but important causative agent of IE in elderly patients with comorbidities.